Inequality in the Spanish Labor Market During the COVID-19 Crisis - Lariau, Ana.; Liu, Lucy Qian. (Washington, D.C. : International Monetary Fund, 2022)
We analyze the differential impact of the COVID-19 crisis on the Spanish labor market across population groups, as well as its implications for income inequality. The main finding is that young, less educated, and low skilled workers, as well as women are the most affected by the COVID-19 shock in terms of job loss rates. The differential impacts were especially acute at the height of the pandemic in 2020 and remain robust after taking into account the heterogeneity of sector characteristics. Given that these vulnerable groups were positioned in the lower end of the income distribution before the crisis, we hypothesize that income inequality likely has increased due to the pandemic. Policies aiming at reducing inequality in the labor market need to go beyond measures that target the hardest-hit sectors and support the vulnerable groups more directly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Human Capital; Aggregate Labor Productivity; Employment; Intergenerational Income Distribution; Unemployment; Wages